2022
DOI: 10.3390/ani12040446
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Emulsification Conditions on Ethanol Extract of Taiwanese Green Propolis Using Polysorbate and Its Immunomodulatory Effects in Broilers

Abstract: Beeswax and resin are the main components of propolis, both of which are hydrophobic. The use of emulsifiers helps to improve the extraction of active propolis compounds and makes them more widely used. In this study, we investigated the optimal parameters for the emulsification of Taiwanese green propolis (TGP) using different polysorbates (polysorbate-20, polysorbate-60, and polysorbate-80) and evaluated the effects on the immunomodulatory response in broilers. The results showed that 4 mg/mL of TGP in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…These results confirmed the results of humoral immunity where elevated expression of IL-2 and interferon—since these cytokines drive antibody formation in birds, they are likely to be a factor in the increased quantities of antibodies generated following antigenic stimulation in propolis-treated birds ( Wang et al, 2006 ). However, this result agreed with Hsiao et al (2022) , who reported that adding propolis to broiler drinking water before and after vaccination upregulates the IL10 . Moreover, Wang et al (2006) found that propolis increases expressions of IL2 and IFN in chickens.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirmed the results of humoral immunity where elevated expression of IL-2 and interferon—since these cytokines drive antibody formation in birds, they are likely to be a factor in the increased quantities of antibodies generated following antigenic stimulation in propolis-treated birds ( Wang et al, 2006 ). However, this result agreed with Hsiao et al (2022) , who reported that adding propolis to broiler drinking water before and after vaccination upregulates the IL10 . Moreover, Wang et al (2006) found that propolis increases expressions of IL2 and IFN in chickens.…”
Section: Discussionsupporting
confidence: 91%
“…These positive effects may be attributed to the immunomodulatory properties of propolis's chemical compounds, such as aromatic acids, alkaloids, flavonoids, polyphenols, and terpenoids, which activate macrophages, promote the production of antibodies, and boost the immune response. In addition, Hsiao et al (2022) reported that adding propolis to broiler drinking water before and after vaccination improves the antibody titer response to infectious bronchitis virus at 28 d of age. This increase in the antibody production suggests that propolis stimulates chicken immune responses and might be utilized to boost antigen-specific antibody responses to vaccinations ( Karpala et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PRO management considerably augmented the points of IgM and IgA in stressed broilers. Three-day supplementation of 300 or 600 µg/mL consistently relieved the higher expression of COX-2, TNF-α, and iNOS mRNA in the spleen ( Hsiao et al, 2022 ). HS can meaningfully increase the IL-10 and IL-4 expression levels for anti-inflammatory cytokines, while co-treated with PRO decreases this elevation ( Hsiao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…After screening the literature, no data are available on the use of NPRL in combating the adverse impacts of cyclic HS on broiler health and performance. Several previous works ( Shalmany and Shivazad 2006 ; Attia et al, 2014 ; Shaddel et al, 2017 ; AL-Kahtani et al, 2022 ; Hsiao et al, 2022 ) have revealed that fortified broiler diets with PRO could be favorable for broiler health and performance via minimizing the inflammation/oxidative stress and boosting the immune function and antioxidant responses. We hypothesized that dietary NPRL would support broiler chickens' health, immunity, and growth performance subjected to cyclic HS.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are ten prenylated flavanone derivatives, and propolins A-J have been isolated from Taiwanese green propolis (TGP) and characterized [ 5 , 12 , 18 , 19 ]. TGP has been reported to have a broad spectrum of biological activities, including those that are anticancer [ 19 ], anti-inflammatory [ 6 , 20 ] and antioxidant [ 5 ]. If we compare TGP with OP, propolin C, D, F, G, and H in TGP are identical to nymphaeol A, nymphaeol B, isonymphaeol B, nymphaeol C, and 3′-geranyl-naringenin in OP, respectively [ 21 ].…”
Section: Introductionmentioning
confidence: 99%